Construction and Validation of Educational Material for Children with Hydrocephalus and Their Informal Caregivers - Tavares, Paloma de Aro J. [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP]; Ferreira, Ana Sílvia S.B.S. [UNESP]; Avila, Marla Andréia G. [UNESP] (Elsevier, 2018)
Objective: To build and validate journal-type digital and printed educational material for informal caregivers (i.e., the parents who provide care) of children with hydrocephalus. Methods: This is a methodologic study conducted in the children's neurosurgery outpatient clinic of a university hospital. The content validity index with a concordance of ≥0.78 was used for validation. Content was validated with the participation of 5 nurses and 3 neurosurgeons, and appearance was validated with the participation of 9 informal caregivers of children with hydrocephalus. Results: A 21-page journal was created to address hydrocephalus and its treatment. The content and semantics of this material were validated with a universal content validity index of 0.90 and 0.98, respectively. Conclusions: Content and appearance of the educational material for informal caregivers of children with hydrocephalus were successfully validated and considered suitable and user-friendly for health education.
Keywords: Caregivers; Health education; Hydrocephalus; Perioperative nursing; Rehabilitation